Internationalization in the media out-of-home industry: the case of JCDecaux in the Brazilian market - Garrido, Antonio Ricardo Ardito; Santos, Ricardo Fernandes; Couto, Marcelo Henrique Gomes; Oliva, Fábio Lotti; Grisi, Celso Cláudio de Hildebrand e (Revista de Administração da UFSM, 2020)
Purpose - This case study aims to understand the motivations for the expansion of the French multinational JCDecaux to Brazil, in the light of relevant theories about the internationalization of companies. JCDecaux is the world’s largest outdoor media company (out of home), a fast-growing industry of the advertising market in Brazil. Design/methodology - This study explain the case based on the internationalization of companies theories, in the economic (Eclectic Paradigm of International Production) and behavioral (Uppsala School and Business Networks Model) strands. In addition to secondary sources, the research was supported by interviews with experts and executives from the outdoor media industry in Brazil. Findings - The main determining drivers for the entry of JCDecaux in the Brazilian market were identified. The analysis based on the theoretical models of internationalization concluded that the economic approach determined in a more significant way the company’s entry into the Brazilian media out of home market. Economic advantages outweighed the costs and risks of Brazil’s business environment, making the country attractive to the company’s foreign investment. Research limitations - The scarcity of data about the media outdoor was reported by a professional interviewed as a negative feature. Another important limitation is the lack of scientific production about the out-of-home media in Brazil. Originality - This paper contributed to generate important information about the Brazilian outdoor media industry, especially on the phenomenon of internationalization of companies in this industry.